PENGARUH KOMPETENSI TERHADAP KINERJA KARYAWAN RUMAH SAKIT SARI MULIA BANJARMASIN - Devi Rusvitawati; Tinik Sugiati; Maya Sari Dewi (Universitas Lambung Mangkurat, 2019)
This study aims to identify and to analyze the influence of achievement and action competency, helping and human services competency, impact and influence competency, managerial competency, cognitive competency, and personal effectiveness competency on job performance of the employees in Sari Mulia Hospital Banjarmasin. There were 310 employees in Sari Mulia Hospital Banjarmasin as the population of the study. Probability sampling with proportional sampling technique was employed as the sampling technique. Data were collected by distributing questionnaires to the samples of 173 employees in Sari Mulia Hospital Banjarmasin. The collected data were analyzed using multiple regressions. Based on the findings of the research, it was found that each variable of competencies, such as achievement and action competency, helping and human services competency, impact and influence competency, cognitive competency, and personal effectiveness competency influence employees’ job performance in Sari Mulia Hospital Banjarmasin